Smart Logistics System in Food Horticulture Industrial Products: a Systematic Review and Future Research Agenda - Rindra Yusianto; Marimin Marimin; Suprihatin Suprihatin; Hartrisari Hardjomidjojo (International Journal of Supply Chain Management, 2020)
Food horticultural commodities are perishable products. Quality decreases rapidly after harvest. Therefore, timely handling and distribution of products must be considered to achieve customer satisfaction. This paper proposes spatial logistics for constructing traceability system framework as a new approach to smart logistics system in food horticulture industrial products. The objective of this article is to analyze existing methods for logistics systems in food horticulture and develop new frameworks for smart logistics systems. The author reviews and synthesizes 115 scientific articles published between 2004 and 2019. Articles reviewed are categorized into sensor Radio Frequency (RF), GPS systems for location and navigation, Internet of Things (IoT) and mobile applications. Most of the previous authors have applied the agricultural product approach. The dominant topic that we found in the literature is IoT, and tracking systems with RFID and remote sensing. Most of the literature focuses on agricultural logistics and there is a lack of discussion about food horticulture industrial product. The contribution of this paper was mapping methods in spatial logistics and logistical traceability and develops new frameworks. For the future agenda, we point to the development of systematic smart logistics that applies intelligent spatial logistic DSS to maintain the logistics system.